2011
DOI: 10.5897/ajb11.1520
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of the random amplified polymorphic DNA (RAPD) marker UBC#116 linked to Fusarium crown and root rot resistance gene (Frl) into a co-dominant sequence characterized amplified region (SCAR) marker for marker-assisted selection of tomato

Abstract: Fusarium crown and root rot of tomato (Solanum lycopersicum) is the disease caused by the fungal pathogen Fusarium oxysporum f.sp. radicis-lycopersici (FORL). The most effective way to control this disease is to plant resistant varieties. Markers tightly linked to Fusarium crown and root rot could be used in breeding programs to introgress crown rot resistance into new varieties. In this study, we converted the random amplified polymorphic DNA (RAPD) marker UBC#116, linked to the Fusarium crown and root rot re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…We then used the published tomato reference genome sequence (Tomato Genome Consortium 2012) (GenBank: GCA_000188115.2 Solyc2.50) as a reference to map sequence reads from both resistant and susceptible parents, and as well as sequences from both bulks. We concentrated on chromosome 9 around the previously published markers that were claimed to be linked to Frl (Truong et al 2011; Mutlu et al 2015). Initially, 1.2 Mb region covering some of the previous markers was taken into account and some of the identified SNVs at the flanking regions were converted to CAPS marker and were then used to map the Frl locus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We then used the published tomato reference genome sequence (Tomato Genome Consortium 2012) (GenBank: GCA_000188115.2 Solyc2.50) as a reference to map sequence reads from both resistant and susceptible parents, and as well as sequences from both bulks. We concentrated on chromosome 9 around the previously published markers that were claimed to be linked to Frl (Truong et al 2011; Mutlu et al 2015). Initially, 1.2 Mb region covering some of the previous markers was taken into account and some of the identified SNVs at the flanking regions were converted to CAPS marker and were then used to map the Frl locus.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic studies showed that Frl is a single dominant locus on chromosome 9 and several molecular markers including the RFLP-based marker TG101 have been shown to be linked to Frl (Truong et al 2011). As thousands of plant lines are screened in a given breeding programmes, marker-assisted selection (MAS) offers advantages over classic phenotype-based selection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation